Hydroxychloroquine blocks SARS-CoV-2 entry into the endocytic pathway in mammalian cell culture - Zixuan Yuan; Mahmud Arif Pavel; Hao Wang; Jerome C. Kwachukwu; Sonia Mediouni; Joseph Anthony Jablonski; Kendall W. Nettles; Chakravarthy B. Reddy; Susana T. Valente; Scott B. Hansen (Communications Biology, 2022)
Super-resolution microscopy in cultured cells is employed to dissect the effect of hydroxychloroquine (HCQ) at the plasma membrane and HCQ directly perturbs clustering of the SARS-CoV-2 receptor ACE2 with endocytic lipids and PIP2 clusters.